(untitled) (Communications in Mathematical Research, 2021)
In this paper, we introduce and study a new system of generalized variational inclusions involving H-η-monotone operators in uniformly smooth Banach spaces. Using the resolvent operator technique associated with H-η-monotone operators, we prove the approximation solvability of solutions using an iterative algorithm. The results in this paper extend and improve some known results from the literature.